2010
DOI: 10.1186/1471-2458-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Partner notification for sexually transmitted infections in developing countries: a systematic review

Abstract: BackgroundThe feasibility and acceptability of partner notification (PN) for sexually transmitted infections (STIs) in developing countries was assessed through a comprehensive literature review, to help identify future intervention needs.MethodsThe Medline, Embase, and Google Scholar databases were searched to identify studies published between January 1995 and December 2007 on STI PN in developing countries. A systematic review of the research extracted information on: (1) willingness of index patients to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
137
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(144 citation statements)
references
References 55 publications
7
137
0
Order By: Relevance
“…The negative feelings expressed by index patients and sexual partners show how complex notifying an STI diagnosis can be to both groups. In this study, the initial idea of index patients of not going to a healthcare center was mentioned, in agreement with the results of other studies (12)(13)(14) . In this study, the initial dilemma of whether to notify the infection to partners or not was similar to the result of another study conducted with patients with HIV infection, which indicated conflicts of interest in partner notification, related to the resulting negative impact and the moral responsibility of notification (7) .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The negative feelings expressed by index patients and sexual partners show how complex notifying an STI diagnosis can be to both groups. In this study, the initial idea of index patients of not going to a healthcare center was mentioned, in agreement with the results of other studies (12)(13)(14) . In this study, the initial dilemma of whether to notify the infection to partners or not was similar to the result of another study conducted with patients with HIV infection, which indicated conflicts of interest in partner notification, related to the resulting negative impact and the moral responsibility of notification (7) .…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with this study, the results of an investigation showed that the intention to notify partners is a challenge to be overcome, due to the stigma associated with STIs, whose failure or success may be influenced by factors such as extramarital sexual relationships, gender identity, structure of power and type of affectional-sexual bond (12) .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations